(untitled) (Economics and region, 2020)
The purpose of the article is to investigate the features of enterprise information security management. The authors determined that information security covers different spheres of activity and aims to form the necessary conditions to support the interests of the enterprise, region, state in the information sphere. The article defines the main varieties of security and the levels at which information security is managed: international, national, enterprise security and personal security. The essence of the concept of information security is defined as a set of strategies for managing processes, tools and policies necessary to prevent, detect, document and counter threats to digital and non-digital information. Information security responsibilities include creating a suite of business processes that will protect information assets, whether formatted, in transit, processed, or dormant. As a result of the research it was determined that the information security management system is a component of the general management system, the basis of which is risk analysis, and the purpose is to create, implement, control and improve measures in the field of information security. An information security management system involves applying a systematic approach to managing enterprise sensitive information so that it remains secure. This system covers people, processes and IT systems. The results of the conducted researches make it possible to conclude that each enterprise is faced with the task of providing a comprehensive plan for information security. Modern information systems are complex sets of technologies (i.e., hardware, software, and firmware), processes, and people working together to enable organizations to process, store, and transmit information in a timely manner to support business and business processes. Prospects for further research are to identify potential areas for minimizing risks and threats to information security, which will ensure not only an appropriate level of competitiveness of the enterprise, but also its further development.